1996
DOI: 10.1071/bt9960421
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Distance From Water and the Soil Seed Bank in a Grazed Semi-Arid Subtropical Rangeland

Abstract: The germinable soil seed bank of a grassy Eucalyptus populnea F.Muell, open woodland was investigated in relationship to distance from water (away from a bore-drain) on North Yancho Station, near Bollon in southern semi-arid Queensland. The germinable soil seed bank was both diverse and abundant, 69 taxa of seedlings being identified to species and 2 more to genus. A mean density of 13 207 ± 4160 seeds m-2 was recorded, with over 80% of the seed being from the annual forbs Crassula sieberana (Schultes & J.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
4
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 22 publications
4
45
4
1
Order By: Relevance
“…The germinable seed bank was dominated by small-seeded species of which a few, i.e., A. praetermissus, H. candolleanum, and T. parvifolia, were overrepresented. A similar pattern was also found in North American deserts (Guo et al 1999) and is often observed in relation to grazing favoring an abundance of annuals that produce numerous seeds (Navie et al 1996;Snyman 2004). In contrast, the seed bank lacked large-seeded species.…”
Section: Seed Bank Compositionmentioning
confidence: 52%
“…The germinable seed bank was dominated by small-seeded species of which a few, i.e., A. praetermissus, H. candolleanum, and T. parvifolia, were overrepresented. A similar pattern was also found in North American deserts (Guo et al 1999) and is often observed in relation to grazing favoring an abundance of annuals that produce numerous seeds (Navie et al 1996;Snyman 2004). In contrast, the seed bank lacked large-seeded species.…”
Section: Seed Bank Compositionmentioning
confidence: 52%
“…For example, soil from grazed woodland in Queensland had more than 13,000 seed m À2 (Navie et al, 1996) and soil from grazed grassland in Victoria had approximately 18,500 seed m À2 (Morgan, 1998). In Europe, seed density was similar for former farmland (12,500 seed m À2 ; Bossuyt et al, 2002) and grasslands (10,000-13,000 seed m À2 ; Milberg and Hansson, 1993;Bakker et al, 1996).…”
Section: Soil Seed Bank Response To Land-use Changementioning
confidence: 93%
“…However, Kinucan and Smeins (1992) and Meissner and Facelli (1999) reported that grazing had no impact on total seed density. In other studies, even an increase of seed density under a higher grazing intensity was found (e.g., Navie et al, 1996;Russi et al, 1992). It can be argued that these contrasting responses were due to differences in species composition and grazing regimes under different climatic condition and at different altitudes.…”
Section: Introductionmentioning
confidence: 90%